Stabilization of marine clay by biomass silica (non-traditional) stabilizers - Marto, Aminaton (2015)
The presence of marine clay in Iskandar Malaysia Region, Nusajaya had caused expensive solutions in the construction of structures and roads. Alternatively, soil treatment is suggested to increase the strength of the unsuitable material to meet the constructions requirement for foundation and also to achieve the specifications for development work. In this study, a series of laboratory test has been conducted to determine the potential of Biomass Silica (BS), one of the commercial brands namely “SH-85” to stabilize marine clay to form the basis of a strong, reliable land for construction of roads and building. Testing program involves obtaining specimens of marine clays from various locations at Iskandar Malaysia Region, followed by laboratory tests to determine the Atterberg limits and Unconfined Compressive Strength (UCS) for treated and untreated of marine clay soils. The proportions of BS added were 3, 6, 9, 12 and 15% and tested at 0, 3, 7 and 28 days curing periods. The results shows that the Plasticity Index (PI) was reduce with increment of BS content. While, an addition of BS content increase in strength treated soils 60 times more than untreated soils, which is gain in early 7 curing days period. This finding indicates the BS is a suitable stabilizer for the marine clay to become strong foundation for construction of road and building.